PENGEMBANGAN MODEL KOMEKS BERMUATAN NILAI-NILAI PENDIDIKAN KARAKTER ASPEK MEMBACA INTENSIF DI SEKOLAH DASAR (Universitas Negeri Semarang, 2012)
Tujuan penelitian ini mendeskripsi karakteristik model Komeks sesuai dengan kebutuhan guru sekolah dasar dan peserta didik, mendeskripsi prinsip-prinsip model Komeks, mengembangkan prototipe buku panduan model Komeks, dan menentukan keefektifan model Komeks bermuatan nilai-nilai pendidikan karakter aspek membaca intensif di sekolah dasar. Penelitian ini menggunakan pendekatan research and development. Sumber data adalah guru-guru dan siswa kelas VI sekolah dasar, ahli model pembelajaran, dan ahli bahasa. Analisis data dilakukan dengan menggunakan deskriptif kualitatif dan kuantitatif sesuai dengan karakteristik data. Karakteristik model Komeks bermuatan nilai-nilai pendidikan karakter aspek membaca berdasarkan kebutuhan siswa dan guru ditinjau dari dimensi sintakmatik, sistem sosial, sistem pendukung, sistem reaksi, dan tujuan instruksional serta dampak pengiring; prinsip-prinsip model Komeks. Hasil uji keefektifan, 34 dari 36 siswa (94%) tuntas dengan nilai rata-rata kelas sebesar 83.06. Model Komeks bermuatan nilai-nilai pendidikan karakter aspek membaca intensif di SD terbukti efektif untuk meningkatkan proses dan hasil belajar peserta didik The aims of this study are: (1) to describe the characteristics of the learning models of Komeks to meet the needs of the teacher of elementary school, (2) to describe the characteristics of the learning model of Komeks to meet the needs of the students, (3) to describe the principle of the learning models of Komeks, (4) to develop prototype of guidelines of the learning model using Komeks, and (5) to determine the model effectiveness of Komeks involving the values of character education in reading intentive aspect in elementary school. Research and development approaches are employed in this research derived from Borg and Gall (1983). The steps are; (1) collecting information and theoretical reviews, (2) desigining the development model, (3) collecting main data in the field, (4) analysing primary data, (5) composing development model, (6) validation, and (7) effectiveness trial. The resource of the data consists of teachers and students of class VI elementary school and the expert of learning model and linguists. The data employes descriptive qualitative and quantitative method.The result shows that the characteristics of the learning model of Komeks involves the values of character education through reading which is based on the students and teachers’ needs. This refers to the systematical dimension, social system, supporting system, reaction system, and instructional purpose and also its impact. Based on its characteristics, the principles of the Komeks learning model are formulated. The test applied in class VI elementary school of Negeri Batursari 5 suggests that there were 34 out of 36 students who successfully have 83.06 score in average. The result of the correation t test was t(0.95)(35 =2.03 . It shows that there is a difference between the application of the model and after it is applied. Thus, it can be concluded that the learning process using the Komeks model is proven to be effective to improve the process of learning and the end result of the students